The primary code: The meanings of John Peel, radio and popular music. (17th October 2007) - Long, Paul
This article evaluates claims about the importance of BBC Radio 1 DJ John Peel in relation to arguments and approaches to the study of music radio. In order to make sense of Peel's meanings and importance, I locate him within a range of modalities and discourses associated with popular music culture and its conjunction with radio. I argue that Peel is best understood not simply through any irreducible or measurable quantification of musical recordings played, genres, moments or artists supported, or even apprehending of their impact or influence. Peel's foregrounding of music as the primary text of music radio is outlined in its conjunction with discourses of authenticity and amateurism attendant upon the context of public service broadcasting. Ultimately, my suggestion in this instance is that Peel can be understood to have demonstrated and represented a particular kind of relationship of radio with music, its consumption, pleasures and meaning, challenging conventional academic approaches that tend to distinguish the two media to the detriment of our conception of both.